FAMILY HISTORY AND SEX INCIDENCE AND RELATION TO SEVERITY IN CHILDHOOD ASTHMA (Iraqi Journal of Medical Sciences, 2004)
Background: Asthma is the most common chronic illness in children and its still raising a lot of concern regarding mortality and morbidity which are still high regardless of the advance of management. Family history of asthma and sex incidence is an interesting issue to be discussed. Aim: Aim of the study is to measure the percentages of positive and negative family history of asthma, sex incidence of asthmatic children and the relation of those two factors to severity. Patients & Method: A total number of 110 patients subjected to study about their family history of asthma and sex of patient and assessment of severity of the attacks of asthma according to specific clinical criteria. Results: The results show that 52.7% were male and 47.2% were female with male/female ratio of 1.115 and there is an increase in moderate to sever asthma in male. Also the results show that 61.8% of patients gave family history of asthma and other allergies and there is no relation between severity and family history of asthma. Conclusion: The prevalence of asthma is more in males and they are more liable for more sever attacks. The asthmatic patients usually have positive family history of asthma but this history does not reflect on severity of asthma. Key words: Asthma, Family History, Sex, Severity Iraqi J Med Sci, 2004; Vol. 3 (10): 85-88